2020
DOI: 10.1177/0340035220944940
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of crowdsourcing for libraries: A case study from Africa

Abstract: Many libraries in the Global South do not collect comprehensive data about themselves, which creates challenges in terms of local and international visibility. Crowdsourcing is an effective tool that engages the public to collect missing data, and it has proven to be particularly valuable in countries where governments collect little public data. Whereas crowdsourcing is often used within fields that have high levels of development funding, such as health, the authors believe that this approach would have many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This project, called Advancing Library Visibility in Africa (ALVA), broadly examines the relationship between public libraries and sustainable development across sub-Saharan Africa. Other components of the project have focused on understanding and building the capacity of African library systems to collect and share data generally (e.g., Lynch et al 2020aLynch et al , 2020bLynch et al , 2020cYoung et al 2020). In contrast, this paper draws on a set of interviews with development practitioners about what types of data libraries were most persuasive in driving their decision-making around partnerships.…”
Section: Methodsmentioning
confidence: 99%
“…This project, called Advancing Library Visibility in Africa (ALVA), broadly examines the relationship between public libraries and sustainable development across sub-Saharan Africa. Other components of the project have focused on understanding and building the capacity of African library systems to collect and share data generally (e.g., Lynch et al 2020aLynch et al , 2020bLynch et al , 2020cYoung et al 2020). In contrast, this paper draws on a set of interviews with development practitioners about what types of data libraries were most persuasive in driving their decision-making around partnerships.…”
Section: Methodsmentioning
confidence: 99%
“…The literature showed different types of research methods that researchers used in areas of crowdsourcing as related to libraries and information services. For instance, Lynch et al (2020) used a survey and focus groups to collect data from the participants. Observation as a research tool was also deemed applicable in a crowdsourcing research (Bassi et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Evans et al (2016) expressed that crowdsourcing enables an organization to benefit from knowledge outside its usual scope. Finally, a more recent study showed that crowdsourcing was recognized as an effective tool to collect missing geographical data about libraries from the public to map libraries in Africa (Lynch et al , 2020).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Libraries engaged in data collection could also leverage access to local populations as "places where a lot of people go" (Participant 5), given some organizations' interest in partners who serve specific populations such as women, youth, or refugees (4 participants). In this way, libraries could fill the gaps that exist in official data in order to furnish information development organizations want but find lacking in other official data sources, as African libraries have done via crowdsourced mapping (Lynch et al, 2020b;Young et al, 2020).…”
Section: Roles For Librariesmentioning
confidence: 99%